Dividing attention in the classroom reduces exam performance. Issue 3 (16th March 2019) - Glass, Arnold L.; Kang, Mengxue
Abstract: The intrusion of internet-enabled electronic devices (laptop, tablet, and cell phone) has transformed the modern college lecture into a divided attention task. This study measured the effect of using an electronic device for a non-academic purpose during class on subsequent exam performance. In a two-section college course, electronic devices were permitted in half the lectures, so the effect of the devices was assessed in a within-student, within-item counterbalanced experimental design. Dividing attention between an electronic device and the classroom lecture did not reduce comprehension of the lecture, as measured by within-class quiz questions. Instead, divided attention reduced long-term retention of the classroom lecture, which impaired subsequent unit exam and final exam performance. Students self-reported whether they had used an electronic device in each class. Exam performance was significantly worse than the no-device control condition both for students who did and did not use electronic devices during that class.